Mathematical Model of Electrodiffusion, Dissociation and Recombination in the Diffusive Layer - Shobukhov, Andrey V.; Savenkova, Nadejda P.; Kuzmin, Runar N.; Maximov, Dmitry S. (Mathematical Modelling and Analysis, 2014)
We study a mathematical model of electrochemical processes in the thin diffusive layer of polymer electrolyte between the electrode and the bulk. We consider diffusion, migration, dissociation and recombination of positive and negative ions in the electric field that take place in this region under various boundary conditions. We demonstrate that the unique stable steady state of the electrochemical system is determined by the ratio of dissociation to recombination. This state attracts time-dependent solutions of the model, but their convergence strongly depends on the electroneutrality of the bulk.